Increased etheno-DNA adducts in affected tissues of patients suffering from Crohn’s Disease, Ulcerative Colitis, and Chronic Pancreatitis - Nair, Jagadeesan; Gansauge, Frank; Beger, Hans; Dolara, Piero; Winde, Günther; Bartsch, Helmut (Antioxidants & redox signaling, 2006)
Antioxidants & Redox Signaling